Infectious disease in the ancient Aegean: Intestinal parasitic worms in the Neolithic to Roman Period inhabitants of Kea, Greece. (February 2018) - Anastasiou, Evilena; Papathanasiou, Anastasia; Schepartz, Lynne A.; Mitchell, Piers D.
Abstract: Little is known about infectious disease and parasites in the prehistoric inhabitants of the islands of the Aegean, in contrast to later time periods. It is only with the development of Greek medical texts in the 5th and 4th centuries BCE we start to find evidence for the diseases that affected the population of region. Foremost amongst these authors was the medical practitioner Hippocrates, who lived on the island of Kos. The descriptions of the many diseases he and his students encountered were recorded in their medical texts in the 4th and 3rd centuries BCE, known as the Hippocratic Corpus. These important texts provided the core philosophy underpinning medical theories in Europe and the Arab world for the following 2, 000 years. Past research to determine which species of intestinal parasitic worms were described in the Hippocratic Corpus has suggested they indicate roundworm, pinworm and Taenia tapeworm. However, until now, there has been no archaeological evidence for which species of helminths were present in ancient Greece. In this study, we analysed soil sediment adherent to the sacrum and iliac bones of the pelvis of 25 burials dating from the Neolithic to Byzantine period on the Greek island of Kea, not far from Kos. Four individuals (16%) were positive for the eggs of intestinal helminths, dating from the Neolithic (4th millennium BCE), Late Bronze Age, and the Roman Period. The species identified were whipworm ( Trichuris trichiura ) and roundworm ( Ascaris lumbricoides ). We consider reasons as to why fewer species of parasite appear to have been present on Kea than was the case for northern Europe at the same time period. This study of ancient parasites shows how we can combine archaeology with history of medicine to better understand the discoveries of key early scientists and medical practitioners. Highlights: This study analysed prehistoric human burials from the island of Kea in Greece. Found evidence for intestinal parasite infection from the Neolithic to the Roman period Compared this archaeological evidence with the 4th–3rd century BCE medical texts of Hippocrates This enabled us to identify some of the parasitic worms described by Hippocrates